The Effect of Toluene Exposure on Central Nervous Disorder among Printing Workers - Marganda, Samuel; Ashar, Taufik; Nurmaini, Nurmaini (Indonesian Journal of Medicine, 2018)
Background: The use of toluene in printing dominates the use of metal chemicals. Toluene is used in 75% of printing work activities. Accumulation of toluene concentrations in printing can cause health problems to workers. The purpose of this study was to analyze the effect of toluene exposure on central nervous system disorders in printing industry workers.Subjects and Method: This study was cross-sectional in the printing industry in Medan, North Sumatra. The population consists of 50 people with consecutive sampling technique sampling. Data on subjective symptoms of central nervous system disorders were measured by the German version of the Q18 questionnaire. The data were analyzed using multiple logistic regression tests.Results: Subjective symptoms of central nervous system disorders increased with tenure ≥2 years (OR = 4.19; p = 0.018) and smoking (OR = 8.91; p = 0.001). Subjective symptoms of central nervous system disorders decreased with age ≤30 years (OR = 0.17; p = 0.004), female sex (OR = 0.50; p = 0.002).Conclusions: The most dominant variable affecting the subjective symptoms of central nervous system disorders is the smoking habit variable with a probability value of 0.92 or 92%.Keywords: subjective symptoms, central nervous system disorders, workers, a printing industryCorrespondence: Samuel Marganda. Department of Environmental Health, Faculty of Public Health, Universitas Sumatera Utara, Medan, North Sumatera. Email: samuelmarganda@yahoo.co.id. Mobile: 085362985340.Indonesian Journal of Medicine (2018), 3(3): 125-133https://doi.org/10.26911/theijmed.2018.03.03.01